How open data and interdisciplinary collaboration improve our understanding of space weather: A risk and resiliency perspective - Ledvina, Vincent E.; Palmerio, Erika; McGranaghan, Ryan M.; Halford, Alexa J.; Thayer, Aidan; Brandt, Laura; MacDonald, Elizabeth A.; Bhaskar, Ankush; Dong, Chuanfei; Altintas, Ilkay; Colliander, James; Jin, Meng; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Space weather refers to conditions around a star, like our Sun, and its interplanetary space that may affect space- and ground-based assets as well as human life. Space weather can manifest as many different phenomena, often simultaneously, and can create complex and sometimes dangerous conditions. The study of space weather is inherently trans-disciplinary, including subfields of solar, magnetospheric, ionospheric, and atmospheric research communities, but benefiting from collaborations with policymakers, industry, astrophysics, software engineering, and many more. Effective communication is required between scientists, the end-user community, and government organizations to ensure that we are prepared for any adverse space weather effects. With the rapid growth of the field in recent years, the upcoming Solar Cycle 25 maximum, and the evolution of research-ready technologies, we believe that space weather deserves a reexamination in terms of a ``risk and resiliency'' framework. By utilizing open data science, cross-disciplinary collaborations, information systems, and citizen science, we can forge stronger partnerships between science and industry and improve our readiness as a society to mitigate space weather impacts. The objective of this manuscript is to raise awareness of these concepts as we approach a solar maximum that coincides with an increasingly technology-dependent society, and introduce a unique way of approaching space weather through the lens of a risk and resiliency framework that can be used to further assess areas of improvement in the field.